Herpetofauna community establishment on the micro habitat as a result of land mines fragmentation in East Kalimantan, Indonesia - TEGUH MUSLIM (Society for Indonesian Biodiversity, 2017)
Muslim T. 2017. Herpetofauna community establishment on the microhabitat as a result of land mines fragmentation in East Kalimantan, Indonesia. Biodiversitas 18: 709-714. Herpetofauna community is established because of habitat suitability or adaptation process that forces a species to survive. In the mining region, herpetofauna habitat change has occurred. The loss of natural habitat and the creation of an artificial habitat result in severance of corridor as a connecting line between herpetofauna habitats so that only microhabitat remains. Microhabitats of herpetofauna survive on limited food resources. The process of surviving of herpetofauna in microhabitats is reflected on the phenomenon of the food chain i.e. reptiles act as predators (top) and amphibians are as preys and as insect predators (middle). In the mining area, an area with a source of water is the destination for all animals, especially herpetofauna, and it even becomes the microhabitat for certain species. The purpose of this study is to determine the species of herpetofauna, its communities and its domination on the water area its microhabitats within the mine area. The exploration is carried out by direct observation (visual encounter surveys). The survey location determination is done intentionally (purposive sampling) on the potential habitat in some locations of water sources, such as pit dam, settling pond, man-made lake (embung), rivers and swamps. Based on the similarity index, there are five species of herpetofauna dominating the life in microhabitats and playing role in the formation of food chain community. Enhydris enhydris and Dendrelaphis pictus are species of snake and act as predator of frog Fejervarya cancrivora and Polypedates leucomystax.